Designing Fractional Task using the PMRI Approach - Ramadhan, M. Hasbi; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi Hasbi (Jurnal Pendidikan Matematika RAFA, 2022)
Fraction was very important to be taught as a basis for learning mathematics for the next stage. This research aimed to design fractions learning for fourth grade students. The method used was design research with type of validation studies which consists three stages, namely the preliminary design, the design experiment, and the retrospective analysis. This research was conducted at Madrasah Ibtidaiyah (MI) in Jambi City with research subjects were eleven students in the fourth grade. Based on the research findings, it was concluded that students really followed the command of questions, so as a teacher or question maker, we must design questions clearly. In addition, students tended to operate fractions starting from addition or subtraction, then multiplication, and lastly division.